Insect transformation with piggyBac: getting the number of injections just right - Shimeld, S; Gregory, M; Alphey, L; Morrison, N (Royal Entomological Society, 2016)
The insertion of exogenous genetic cargo into insects using transposable elements is a powerful research tool with potential applications in meeting food security and public health challenges facing humanity. piggyBac is the transposable element most commonly utilised for insect germline transformation. The described efficiency of this process is variable in published literature, and a comprehensive review of transformation efficiency in insects is lacking. This study compares and contrasts all available published data to a comprehensive data set provided by a biotechnology group specialising in insect transformation. Based on analysis of these data, with particular focus on the more complete observational data from the biotechnology group, we have designed a decision tool to aid researchers’ decision-making when using piggyBac to transform insects by microinjection. A combination of statistical techniques are used to define appropriate summary statistics of piggyBac transformation efficiency by species and insect order. Publication bias is assessed by comparing the datasets. The bias is assessed using strategies co-opted from the medical literature. The work culminates in building the Goldilocks decision tool, a Markov-Chain Monte-Carlo simulation operated via a graphical interface and providing guidance on best practice for those seeking to transform insects using piggyBac.